Ciudad física y ciudad representada: discapacidad, justicia espacial e innovación social. / Physical and represented city: disability, spatial justice and social innovation - ARENAS, Andrea del Pilar; CASTELLANOS-GARCÍA, Gloria Esperanza; ALDANA-PORRAS, Juan Manuel (Utopía y Praxis Latinoamericana, 2020)
RESUMEN El objetivo del presente artículo es socializar los resultados de un proceso de investigación sobre las experiencias cotidianas del sujeto en situación de discapacidad en torno a la construcción del derecho a la ciudad, para el desarrollo de una aplicación móvil de identificación de espacios accesibles en Ibagué. Se utilizó una metodología mixta y de sección cruzada en la que participaron treinta personas, logrando identificar la vivencia y apropiación de la ciudad desde las categorías accesibilidad y justicia espacial. Así mismo, cómo la aplicación se constituyó en un proceso de innovación social tendente a promover la inclusión y participación comunitaria.ABSTRACT The objective of this article is to socialize the results of a research process on the daily experiences of the subject in a disability situation around the construction of the right to the city, for the development of a mobile application to identify accessible spaces in Ibagué. A mixed and cross-section methodology was used in which thirty people participated, managing to identify the experience and appropriation of the city from the accessibility and spatial justice categories. Likewise, how the application was constituted in a process of social innovation tending to promote community inclusion and participation.